Barium sulfate crystallization dependence on upper rim calix[4]arene functional groups - Baynton, A.; Ogden, Mark; Raston, C.; Jones, Franca (The Royal Society of Chemistry, 2012)
Although the effects of p-sulfonated and p-phosphonated calix[4]arene on barium sulfate morphology are similar, their ability to form mesocrystals of material are markedly different. The p-phosphonated calix[4]arene results in the formation of fibre bundles similar to those previously observed during barium sulfate crystallization in the presence of di-block copolymers. The isostructural sulfonated calix[4]arene, however, affords material consistent with the initial formation of mesocrystals which subsequently fuse. This material shows significant beam damage when viewed under a transmission electron microscope (TEM) suggesting incorporation of the sulfonated calix[4]arene, although there was no evidence of this from X-ray diffraction and atomic force microscopy (AFM) studies. We hypothesise that this calixarene is incorporated without significant change in structure of the material, and that the interaction of the macrocycle with the barium sulfate lattice is sufficiently weak that surface AFM imaging is effective in removing it from the surface.